Macrocycle‐based differential sensing: Design strategies and applications - Jia‐Hong Tian; Zhe Zheng; Yu‐Chen Pan; Yuefei Wang; Dong‐Sheng Guo (Responsive Materials)
Abstract Differential sensing, inspired by the olfactory systems in mammals, utilizes the cross‐reactivity of multiple sensor units toward analytes to generate a distinctive fingerprint for each analyte. Widely acknowledged as a robust analytical technique, differential sensing has entered a flourishing era with the advancement of machine learning. Nevertheless, developing sensor units and optimizing signal transduction remain significant tasks left to chemists. Macrocyclic receptors serve as promising materials for constructing sensor arrays with enhanced cross‐reactivity, facilitated by their ease of synthesis and derivatization, inherent broad‐spectrum encapsulation capability, and compatibility with multiple responsive signal transduction approaches. Herein, we present a concise overview of the fundamental processes involved in a sensor array, encompassing array construction, signal transduction, and data acquisition and analysis, with an emphasis on the unique advantages provided by macrocyclic receptors in the former two aspects. Then, we present fascinating application scenarios where macrocyclic receptors shine in differential sensing that rely on various ingenious sensing strategies. Finally, we discuss several issues with potential improvement and future directions for macrocyclic receptor‐based differential sensing, offering a forward‐looking perspective.